Incidence Picture of Early Loss of Primary First Molar Teeth in 6-9 Year Old Children in Dental Hospital of Jember University - Ilham Nur Iman Baihaqi; Surartono Dwiatmoko; Dyah Setyorini (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Premature loss of primary teeth is a condition where primary teeth are lost before the replacement teeth approach eruption due to caries, trauma and systemic conditions. Premature date can lead to a reduction in the length of the dental arch and migration of the opposing teeth leading to rotation, crowding and impaction of the permanent teeth. The purpose of the study: to describe the incidence picture of early loss of primary first molar teeth in 6-9 year old children in dental hospital of Jember University. The type of research carried out in this study was descriptive observational with a cross sectional approach. The research data showed that there were 42 medical records of pediatric patients aged 6-9 years. There are 5 medical records for patients aged 6 years, 15 data for medical colleagues for patients aged 7 years, 16 medical records for patients aged 8 years, and 6 medical records for patients aged 9 years. The percentage incidence of premature date of the maxillary right primary first molar was 11.9%, the premature date of the maxillary left first molar was 9.5%, while the mandibular left first primary molar had a premature date of 7.1%, and in the premature date of the mandibular right primary first molar was 19.05%. The conclusion from the results of this study is that the incidence of premature first molar dates in children aged 6-9 years at RSGM UNEJ in 2020 is most commonly found in the mandibular right first molar at 19.05%